Uji Beberapa Konsentrasi Piper aduncum L. Ekstrak Daun Untuk Kontrol Leptocorisa oratorius Fabricius (Hemiptera, Alydidae) Tanaman Padi (Oryza sativa L.) - Joko Karsidi; Rusli Rustam; Jeltje Hennie Laoh (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Leptocorisa oratorius F. is a major pest of  rice plant, that can damage the rice plant by sucking the liquid from the cells of the rice plant. For controlling this pest usually used synthetic chemical insecticide but this can cause negative impacts such pest resistance and pest resurgence. The use of leaf extract of Piper aduncum L. as a botanical insecticide is suittable to control Leptocorisa oratorius. The experiment was conducted at Laboratory of Plant Pest and Agribusiness Incubator University  of Riau Pekanbaru, from February to April 2013. The experiment used a Completely Randomized Design (CRD) with 5 treatments and 4 replications. The treatmens are (Piper aduncum leaf extract are: 0 g/l water,  25 g/l water, 50 g/l water, 75 g/l water, and 100 g/l of water. Aplication of Piper aduncum leaf extract at treatment 75 g/l water was able to kill Leptocorisa oratorius up to 90%. Number concentration is still in the range of LC 95 values  from 7,2 to 21,9%. The exact concentration to kill 95% of the Leptocorisa oratorius is 10,1% or equitvalent to 101 g/l of water.   Keyword: Rice, Leptocorisa oratorius, Peper aduncum L.